Implementasi Sistem Informasi Reservasi Event Berbasis Web - Wahyuni, Ayu Dewi Sri Wahyuni; Adli, Idham Abdi Al; Sahrul, Nizar; Nurajizah, Siti; Syabaniah, Rifa Nurafifah; Yulianti, Ita (AI Society & STMIK Indonesia, 2025)
The hospitality industry currently experiencing rapid development in line with advances is information technology, which drive operational efficiency and enhance customer satisfaction. Amaris Hotel Tasikmalaya faces challenges in its event reservation process, which is still conducted manually, often resulting in delays, recording errors, and suboptimal data management. This study aims to develop and implement a web basesd Event Reservation Information System to address these issues. The methodology used is the waterfall model, covering requirements analysis, design, implementation, testing, and maintenance. The developed system provides features for event data management, scheduling, reservations, and reporting, accessible online by both hotel and customers. Internal testing results indicate that the system can accelerate the reservation process, reduce, data entry errors, and improve data management efficiency. The system also provides ease of access and information transparency for customers and supports hotel management decision making. With the implementation of this system, service quality and customer satisfaction are expected to improve.